[1]5a\6b平方c-7b\12ac平方+11c\8a平方b [2]2\2a+3+3\3-2a+2a+15\4a平方-9【3】1\x平方-4x+4-x\x平方-4+1\2x+4 【4】1+ [ 3\a-2]÷a+1\a平方-4

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 15:34:13
[1]5a\6b平方c-7b\12ac平方+11c\8a平方b[2]2\2a+3+3\3-2a+2a+15\4a平方-9【3】1\x平方-4x+4-x\x平方-4+1\2x+4【4】1+[3\a-2]

[1]5a\6b平方c-7b\12ac平方+11c\8a平方b [2]2\2a+3+3\3-2a+2a+15\4a平方-9【3】1\x平方-4x+4-x\x平方-4+1\2x+4 【4】1+ [ 3\a-2]÷a+1\a平方-4
[1]5a\6b平方c-7b\12ac平方+11c\8a平方b [2]2\2a+3+3\3-2a+2a+15\4a平方-9
【3】1\x平方-4x+4-x\x平方-4+1\2x+4 【4】1+ [ 3\a-2]÷a+1\a平方-4

[1]5a\6b平方c-7b\12ac平方+11c\8a平方b [2]2\2a+3+3\3-2a+2a+15\4a平方-9【3】1\x平方-4x+4-x\x平方-4+1\2x+4 【4】1+ [ 3\a-2]÷a+1\a平方-4
[1]5a\6b平方c-7b\12ac平方+11c\8a平方b
=(20a³c-14ab³+33bc³)/24a²b²c²
[2]2\2a+3+3\3-2a+2a+15\4a平方-9
=【2(2a-3)-3(2a+3)+15]/(4a²-9)
=-2a/(4a²-9)
【3】1\x平方-4x+4-x\x平方-4+1\2x+4
=1/(x-2)²-x/(x+2)(x-2)+1/2(x+2)
=[2x(x+2)-2x(x-2)+(x-2)²]/2(x+2)(x-2)²
=(x²+4x+4)/2x(x+2)(x-2)²
=(x+2)/2x(x-2)²
【4】1+ [ 3\a-2]÷a+1\a平方-4
看不懂你的式子